Logics of action and models of capitalism: Explaining bottom‐up non‐liberal change. Issue 3 (12th March 2014) - Etienne, Julien; Schnyder, Gerhard
Abstract: Recent institutionalist scholarship has theorized the liberalization or "disorganization" of capitalism as the result of shifts in economic actors' "logic of action" towards opportunism. Little attention has been given to the reverse possibility that shifts in economic actors' "logic of action" away from opportunism might contribute to "embedding" or "organizing" capitalism. This paper builds on recent scholarship to theorize this scenario and then demonstrate its empirical validity with an historical institutionalist study of the emergence of such a "non‐liberal" institution in Switzerland in 1961. The theoretical framework links three "logics of action" – opportunism, enlightened self‐interest and strong solidarity – to Höpner's typology of capitalist institutions – organized, coordinated, and liberal. It theorizes the interactions between these logics and the social mechanism – goal signaling – that can explain a shift from one logic of action to another, potentially leading to change from one type of institution to another.